Determination of pervious concrete mix by strength. Issue 1 (March 2020) - Huang, Bo-Syun; Li, Yan-Fu; Wu, Chi-Hsing; Tang, Chi
Abstract: The paper first used a cement amount C =300 kg and a range of water-cement ratio W/C =0.36∼0.44 to make pervious concrete specimens of different W/C to perform the compressive strength and the flexural strength tests, as well as the permeability coefficient and the porosity tests. These tests were to find the W/C of the maximum strength under meeting the requirements of permeability and water retention. The concrete mix corresponding to the W/C determined this way can be treated as the optimal mix since it gives the maximum strength for a cement amount C =300 kg. Then, similar tests were performed for C =350 kg to determine its optimal mix. From which, the relationship of the strength of the optimal mix vs C is established.